Preparation method of unidirectional heat-conducting polyurethane foam

By introducing BN and CNT, and using PDA modification and Fe3O4 grafting technology, magnetic thermal conduction nanoparticles PBC@Fe3O4 are formed, and a one-way thermal conduction polyurethane foam is prepared, which solves the problem of integrating heat dissipation/heat insulation functions in the prior art, and achieves efficient heat dissipation and excellent heat insulation performance.

CN119875356APending Publication Date: 2025-04-25SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882945.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult to integrate the heat dissipation/insulation function in the electronic and electrical industry, especially when it is necessary to simultaneously protect electronic components from high temperature shocks and effectively dissipate heat.

Method used

By introducing boron nitride (BN) and carbon nanotubes (CNT), the thermally conductive nanoparticles were modified with polydopamine (PDA), and the Fe3O4 magnetic particles were grafted on the surface of the thermally conductive nanoparticles through hydrothermal reaction to form magnetic thermally conductive nanoparticles PBC@Fe3O4. It is added to the polyurethane synthesis system and applied to a magnetic field to form a polyurethane composite material with a continuous gradient distribution of thermal nanoparticles. Then, a one-way thermally conductive polyurethane foam is prepared by supercritical carbon dioxide foaming method.

Benefits of technology

The integrated heat dissipation/heat insulation function of polyurethane foam is achieved, meeting the needs of the electronic and electrical industry, and the thermal conductivity coefficient of the thermal conductivity surface is significantly improved, while the thermal insulation surface still maintains excellent thermal insulation performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of unidirectional heat-conducting polyurethane foam, which is characterized by comprising the following steps of: utilizing excellent heat conductivity of boron nitride (BN), introducing a carbon nanotube (CNT) to play a bridging role between BN sheet layers, and modifying heat-conducting nano particles by adopting polydopamine (PDA) to improve the interface interaction between the heat-conducting nano particles and a polyurethane matrix so as to obtain modified heat-conducting nano particles PBC; then, Fe3O4 magnetic particles are grafted to the surface of PBC through a hydrothermal reaction, and magnetic heat conduction nanoparticles PBC coated Fe3O4 are obtained; the preparation method comprises the following steps: adding the magnetic heat-conducting nanoparticles into a polyurethane synthesis system, applying a magnetic field effect, and migrating and orienting the magnetic heat-conducting nanoparticles along the direction of the magnetic field in monomer reaction and system polymerization viscosity-changing processes to form a polyurethane composite material with the content of the heat-conducting nanoparticles in continuous gradient distribution; the polyurethane foam is further foamed by a supercritical carbon dioxide foaming method (scCO2), so that the polyurethane foam of which the cell size and the heat-conducting property are in continuous gradient distribution can be obtained, and the integration of heat dissipation and heat insulation functions is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing unidirectional heat-conducting polyurethane foam, belonging to the field of polymer preparation. Background Art

[0002] Polyurethane foam material is one of the main varieties of polyurethane synthetic materials. Due to its porous structure, low thermal conductivity and other characteristics, it exhibits excellent wear resistance, tear resistance, chemical corrosion resistance, shock resistance, pressure resistance, heat insulation and other excellent properties, and is widely used. When polyurethane foam is used in the field of electronic and electrical industry, in a specific environment, in addition to its excellent heat insulation effect, it is necessary to protect electronic equipment and components from high temperature impact. At the same time, the heat accumulated during use and the heat generated by electronic components need to be promptly discharged and dissipated to avoid failure of the equipment due to excessive internal temperature. Therefore, it is necessary to construct a gradient unidirectional heat conduction structure of polyurethane foam, that is, the contact surface with the high temperature environment has excellent heat insulation effect, and the contact surface with the protected electronic components has good heat conduction and heat dissipation function, so as to realize the integration of heat dissipation / heat insulation function.

[0003] Wang Bing, Ji Haifeng, et al., Polymer Materials Science and Engineering, 2022, 38(9): 66. L-lysine (Lys) functionalized grafted boron nitride nanosheets (Lys@BNNS) were prepared by combining mechanical sanding exfoliation with non-covalent surface modification. Thermoplastic polyurethane (TPU) composites were obtained by solution blending using Lys@BNNS as fillers. When the filler mass fraction reached 5%, the thermal conductivity of the TPU composite increased to 0.52 W·m -1 ·K -1 , which is 160% higher than pure TPU; Xue Yaozong, Zhao Yujin, et al., New Chemical Materials, 2024, 52(5): 120, Boron nitride (BN) was modified by amino modification with γ-aminopropyltriethoxysilane (KH-550), and the modified thermal conductive filler was in-situ polymerized with waterborne polyurethane (WPU) emulsion, and the WPU composite film was obtained after drying at room temperature. When the addition amount of the modified filler was 15%, the thermal conductivity of the composite film was 0.621 W·m -1 ·K -1 , which is about 34 times that of pure WPU film. However, there is no report on thermally conductive polyurethane foam and polyurethane foam with gradient unidirectional thermal conductive structure. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a unidirectional heat-conducting polyurethane foam in view of the deficiencies of the prior art. The method is characterized in that the excellent thermal conductivity of boron nitride (BN) is utilized, carbon nanotubes (CNT) are introduced to play a bridging role between BN sheets, polydopamine (PDA) is used to modify heat-conducting nanoparticles to enhance the interface effect between the nanoparticles and the polyurethane matrix, thereby obtaining modified heat-conducting nanoparticles PBC; Fe3O4 magnetic particles are then grafted onto the surface of PBC by a hydrothermal reaction, thereby obtaining magnetic heat-conducting nanoparticles PBC@Fe3O4; the nanoparticles are added to a polyurethane synthesis system, and a magnetic field is applied. During the monomer reaction and the system polymerization and viscosity-changing process, the magnetic heat-conducting nanoparticles migrate and orient along the direction of the magnetic field, thereby forming a polyurethane composite material with a continuous gradient distribution of the content of the heat-conducting nanoparticles; the polyurethane composite material is further foamed by a supercritical carbon dioxide foaming method (scCO2), thereby obtaining a polyurethane foam with a continuous gradient distribution of the pore size and the thermal conductivity, thereby realizing the integration of heat dissipation / heat insulation functions.

[0005] The object of the present invention is achieved by the following technical measures, wherein the raw material fractions are all parts by weight unless otherwise specified.

[0006] A method for preparing a unidirectional heat-conducting polyurethane foam comprises the following steps:

[0007] Preparation of PBC@Fe3O4 magnetic thermal conductive nanoparticles:

[0008] Weigh 5-50 parts of BNNS and 1-12 parts of CNT and disperse them in 500-5000 parts of a mixed solution of ethanol / deionized water with a volume ratio of 1 / 1, ultrasonicate at 30-90° C. for 0.5-2 hours, then add 1.3-13 parts of dopamine hydrochloride (DA), adjust the pH value to 8.5 with trishydroxymethylaminomethane, react at room temperature for 6-20 hours, wash with water, and dry to obtain PBC;

[0009] Weigh 5-50 parts of PBC and dissolve it in 500-5000 parts of deionized water at 30-90°C for 0.5-2h, add 1.5-15 parts of ferric chloride, 0.5-10 parts of ferrous chloride and 5-50 parts of 1,6-hexanediamine, stir vigorously at 30-90°C for 2-10h, wash with water, and dry to obtain magnetic thermal conductive nanoparticles PBC@Fe3O4;

[0010] Preparation of unidirectional heat-conducting polyurethane foam:

[0011] A one-step method is used to prepare a unidirectional thermal conductive polyurethane composite material in situ: first, 100 parts of a macromolecular polyol, 0.2-5 parts of a chain extender and 5-50 parts of the above-mentioned PBC@Fe3O4 magnetic thermal conductive nanoparticles are weighed, and the mixture is evenly stirred, vacuum dehydrated at 100-130°C for 2-4 hours, cooled to 50-80°C, 10-50 parts of a polyisocyanate are quickly added, and the mixture is quickly stirred and poured into a polytetrafluoroethylene mold, and a magnetic field is applied with a magnetic field strength of 30-300mT, and the mixture is vacuum baked at 100-150°C, and then cooled to 90-140°C for aging for 10-20 hours to obtain a unidirectional thermal conductive TPU / PBC@Fe3O4 composite material; wherein the macromolecular polyol is a hydroxyl-terminated polyhexanediol. At least one of ethylene glycol ester (PEA), terminal hydroxyl polycaprolactone (PCL), terminal hydroxyl polyhexane adipate (PHA), terminal hydroxyl polybutylene adipate (PBA), polytetramethylene ether glycol (PTHF), and polypropylene glycol, and the average molecular weight thereof is 500-3000; the polyisocyanate is at least one of toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), and 1,4-cyclohexane diisocyanate (CHDI); the chain extender is at least one of 1,4-butanediol, ethylene glycol, propylene glycol, diethylene glycol, and 1,4-cyclohexanol;

[0012] The TPU / PBC@Fe3O4 composite material is placed in a high-temperature and high-pressure foaming kettle preheated to 60-120°C for supercritical carbon dioxide (scCO2) foaming. The pressure in the kettle is 10-20MPa. CO2 saturation is performed for 2-10 hours, and then the pressure is quickly released. The sample is taken out and quickly water-cooled to shape the bubbles, thereby obtaining a unidirectional heat-conducting TPU / PBC@Fe3O4 composite foam.

[0013] The present invention has the following advantages

[0014] The present invention obtains a unidirectional heat-conducting polyurethane foam by innovating the construction of a gradient structure of the polyurethane heat-conducting foam and the preparation method, realizes the integration of heat dissipation / heat insulation functions, meets the needs of the electronic and electrical industry, and has the following advantages:

[0015] Boron nitride (BN) has excellent thermal conductivity, and carbon nanotubes (CNTs) are introduced to play a bridging role between BN sheets. Polydopamine (PDA) is used to modify thermal conductive nanoparticles, which are bonded to the surface of BN nanosheets through π-π stacking and hydrogen bonding to enhance the interface between the nanoparticles and the polyurethane matrix. Subsequently, Fe3O4 magnetic particles are grafted onto the surface of the thermal conductive particles through a hydrothermal reaction to obtain magnetic thermal conductive nanoparticles PBC@Fe3O4.

[0017] · Adding magnetic thermal conductive nanoparticles PBC@Fe3O4 into the polyurethane synthesis system and applying a magnetic field, since the viscosity of the polymerization system is low at the initial stage of the reaction, the magnetic thermal conductive nanoparticles are easy to migrate and orient along the direction of the magnetic field, which is conducive to the formation of a polyurethane composite material with a continuous gradient distribution of thermal conductive nanoparticles;

[0020] In the supercritical carbon dioxide foaming method (scCO2) of gradient polyurethane composite materials, on the side with higher content of thermally conductive nanoparticles, due to the pore nucleation effect of the nanoparticles and the increased viscosity of the system, which hinders the growth of pores, the pore size is smaller, the pore density is lower, and the solid part is more. In addition, the thermal conductive network formed by the thermally conductive nanoparticles gives it a higher thermal conductivity coefficient; on the side with lower content of thermally conductive nanoparticles, the system viscosity is lower, the foaming ratio is higher, the pore size is larger, and the thermal insulation performance is excellent, thereby forming a unidirectional thermally conductive polyurethane foam with a continuous gradient distribution of pore structure and thermal conductivity. DETAILED DESCRIPTION

[0022] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the contents of the present invention described above.

[0023] Example 1

[0024] 20 parts of BNNS and 5 parts of CNT were weighed and dispersed in 3000 parts of a mixed solution of ethanol / deionized water with a volume ratio of 1 / 1, and ultrasonicated at 70°C for 1 hour, followed by adding 6.5 parts of dopamine hydrochloride (DA), adjusting the pH value to 8.5 with tris(hydroxymethyl)aminomethane, reacting at room temperature for 10 hours, and washing with water and drying to obtain PBC;

[0025] Weigh 20 parts of PBC and add them to 2000 parts of deionized water at 70°C for 1 hour, add 6 parts of ferric chloride, 3 parts of ferrous chloride and 20 mL of 1,6-hexanediamine, stir vigorously at 50°C for 6 hours, wash with water and dry to obtain magnetic thermal conductive nanoparticles PBC@Fe3O4;

[0026] A one-step method was used to prepare a unidirectional thermal conductive polyurethane composite material in situ: first, 100 parts of hydroxyl-terminated polyethylene adipate (PEA) with a molecular weight of 2000, 0.5 parts of 1,4-butanediol and the above-mentioned 20 parts of PBC@Fe3O4 magnetic thermal conductive nanoparticles were weighed, stirred evenly, vacuum dehydrated at 100°C for 4 hours, cooled to 60°C, and quickly added with 20 parts of 4,4'-diphenylmethane diisocyanate (MDI). After rapid stirring, the mixture was poured into a polytetrafluoroethylene mold, and a magnetic field was applied with a magnetic field strength of 100mT. The mixture was vacuum baked at 120°C, and then cooled to 100°C for aging for 15 hours to obtain a unidirectional thermal conductive TPU / PBC@Fe3O4 composite material.

[0027] The TPU / PBC@Fe3O4 composite material was placed in a high-temperature and high-pressure foaming reactor preheated to 100°C for supercritical carbon dioxide (scCO2) foaming. The pressure in the reactor was 15MPa, and CO2 saturation was performed for 6 hours. Then the pressure was quickly released, the sample was taken out, and the foam cells were quickly cooled with water to shape the foam. The unidirectional heat-conducting TPU / PBC@Fe3O4 composite foam was obtained, and the thermal conductivity of the thermal conductive surface reached 2.39W·m -1 ·K -1 The thermal conductivity of the insulation surface is 0.16W·m -1 ·K -1 .

[0028] Example 2

[0029] 30 parts of BNNS and 7 parts of CNT were weighed and dispersed in 4000 parts of a mixed solution of ethanol / deionized water with a volume ratio of 1 / 1, and ultrasonicated at 60°C for 1.5 hours, followed by adding 8 parts of dopamine hydrochloride (DA), adjusting the pH value to 8.5 with tris(hydroxymethyl)aminomethane, reacting at room temperature for 12 hours, and washing with water and drying to obtain PBC;

[0030] Weigh 30 parts of PBC and add them to 4000 parts of deionized water for ultrasonic treatment at 60°C for 1 hour, add 9 parts of ferric chloride, 4.5 parts of ferrous chloride and 30 mL of 1,6-hexanediamine, stir vigorously at 70°C for 4 hours, wash with water and dry to obtain magnetic thermal conductive nanoparticles PBC@Fe3O4;

[0031] A one-step method was used to prepare a unidirectional thermal conductive polyurethane composite material in situ: first, 100 parts of hydroxy-terminated polybutylene adipate (PBA), 1 part of ethylene glycol and the above 30 parts of PBC@Fe3O4 magnetic thermal conductive nanoparticles were weighed, stirred evenly, vacuum dehydrated at 110°C for 4 hours, cooled to 55°C, 30 parts of polyisocyanate were quickly added, quickly stirred evenly, poured into a polytetrafluoroethylene mold, and a magnetic field was applied with a magnetic field strength of 150mT, vacuum baked at 130°C, and then cooled to 110°C for aging for 12 hours to obtain a unidirectional thermal conductive TPU / PBC@Fe3O4 composite material;

[0032] The TPU / PBC@Fe3O4 composite material was placed in a high-temperature and high-pressure foaming reactor preheated to 110°C for supercritical carbon dioxide (scCO2) foaming. The pressure in the reactor was 18MPa, and CO2 saturation was performed for 4h. Then the pressure was quickly released, the sample was taken out, and it was quickly water-cooled to shape the pores. The unidirectional heat-conducting TPU / PBC@Fe3O4 composite foam was obtained, and the thermal conductivity of the thermal conductive surface reached 2.98W·m -1 ·K -1 The thermal conductivity of the insulation surface is 0.11W·m -1 ·K -1 .

Claims

1. A unidirectional heat-conducting polyurethane foam, characterized in that The preparation and molding method of the polyurethane foam comprises the following steps: Preparation of PBC@Fe3O4 magnetic thermal conductive nanoparticles: Weigh 5-50 parts of BNNS and 1-12 parts of CNT and disperse them in 500-5000 parts of a mixed solution of ethanol / deionized water with a volume ratio of 1 / 1, ultrasonicate at 30-90° C. for 0.5-2 hours, then add 1.3-13 parts of dopamine hydrochloride (DA), adjust the pH value to 8.5 with trishydroxymethylaminomethane, react at room temperature for 6-20 hours, wash with water, and dry to obtain PBC; Weigh 5-50 parts of PBC and dissolve it in 500-5000 parts of deionized water at 30-90°C for 0.5-2h, add 1.5-15 parts of ferric chloride, 0.5-10 parts of ferrous chloride and 5-50 parts of 1,6-hexanediamine, stir vigorously at 30-90°C for 2-10h, wash with water, and dry to obtain magnetic thermal conductive nanoparticles PBC@Fe3O4; Preparation of unidirectional heat-conducting polyurethane foam: A one-step method is used to prepare a unidirectional thermal conductive polyurethane composite material in situ: first, 100 parts of a macromolecular polyol, 0.2-5 parts of a chain extender and 5-50 parts of the above-mentioned PBC@Fe3O4 magnetic thermal conductive nanoparticles are weighed, and the mixture is evenly stirred, vacuum dehydrated at 100-130°C for 2-4 hours, cooled to 50-80°C, 10-50 parts of a polyisocyanate are quickly added, and the mixture is quickly stirred and poured into a polytetrafluoroethylene mold, and a magnetic field is applied with a magnetic field strength of 30-300mT, and the mixture is vacuum baked at 100-150°C, and then cooled to 90-140°C for aging for 10-20 hours to obtain a unidirectional thermal conductive TPU / PBC@Fe3O4 composite material; wherein the macromolecular polyol is a hydroxyl-terminated polyhexanediol. At least one of ethylene glycol ester (PEA), terminal hydroxyl polycaprolactone (PCL), terminal hydroxyl polyhexane adipate (PHA), terminal hydroxyl polybutylene adipate (PBA), polytetramethylene ether glycol (PTHF), and polypropylene glycol, and the average molecular weight thereof is 500-3000; the polyisocyanate is at least one of toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), and 1,4-cyclohexane diisocyanate (CHDI); the chain extender is at least one of 1,4-butanediol, ethylene glycol, propylene glycol, diethylene glycol, and 1,4-cyclohexanol; The TPU / PBC@Fe3O4 composite material is placed in a high-temperature and high-pressure foaming kettle preheated to 60-120°C for supercritical carbon dioxide (scCO2) foaming. The pressure in the kettle is 10-20MPa. CO2 saturation is performed for 2-10 hours, and then the pressure is quickly released. The sample is taken out and quickly water-cooled to shape the bubbles, thereby obtaining a unidirectional heat-conducting TPU / PBC@Fe3O4 composite foam.